EPIPHYTIC LICHENS OF NATURAL AND ARTIFICIAL FOREST PLANTATIONS OF YELANETSKO-INGULSKIY REGION (THE MYKOLAYIV AND KIROVOHRAD REGION, UKRAINE) - Boyko, T. O. (Forestry and Forest Melioration, 2018)
The Yelanetsko-Ingulskiy region is located in the basin of Southern Bug river in-between rivers Hnylyi Yelanets and Ingul. The studied area is about 2240 km2. Administratively it covers the northern part of the Mykolayiv region and southeast of the Kirovohrad region. According to the geobotanical subdivision of Ukraine, the Yelanetsko-Ingulskiy region lies within the Dnieper-Bug (Kryvyi Rih) district of motley-grass cereal steppes, gullies forests and vegetation of granite outcrops. The northern border lies between the steppe and forest steppe zones. In the south, the territory borders Buh-Ingulsk district of cereal steppes, hearth meadows, and limestone outcrop vegetation. Physical and geographical features of the region, its geological structure, climate and other natural factors led to the formation of a large variety of lichen biota. Results The combination of natural vegetation and artificial plantations contributed the spread of epiphytic lichens in the region. A large number of artificial forest plantations contribute the spread of epiphytic lichens. In particular, 39 species (18.6 %) of lichens are growing on the bark of trees and shrubs. Leading positions in a systematic structure of epiphytes of Yelanetsko-Ingulskiy region occupied by families Parmeliaceae Zenker, Physciaceae Zahlbr., Lecanoraceae K?rb. and Teloschistaceae Zahlbr., and also families Physcia (Schreb.) Michx. and Lecanora Ach. Artificial plants (artificial forests, shelterbelts, gardens, parks and others) play an important role in the spread of epiphytic lichens of the Yelanetsko-Ingulskiy region. Species composition and occurrence of epiphytic lichen cover in forest belts are determined by their age, construction and structure of plantations and their distance from roads. Overall lichen biota of belts has 21 species of lichens, between which representatives of the families Lecanora, Physcia, Pleurosticta Petr., Rinodina (Ach.) Gray, Scoliciosporum A. Massal., Xanthoria (Fr.) Th. Fr are dominated. In general, an epiphytic complex of belts consists of species that are resistant to moisture stress and air pollution. Lichen biota of parks and gardens has a similar species composition of lichens, which generally includes 27 species of lichens. At the territory of the Yelanetsko-Ingulskiy region, areas of artificial forest plantations often occur, amounted 29 species, among which Pleurosticta acetabulum (Neck.) Elix & Lumbsch, Physcia adscendens, Ph. tenella (Scop.) DC., Pseudevernia furfuracea (L.) Zopf, Ramalina pollinaria (Westr.) Ach. form a significant coverage. In the north of the region, forest shlterbelts with dominating Quercus robur are occasionally presented; on the bark of the oak trees we found 23 species of lichens (Lecania cyrtella (Ach.) Th. Fr., Lecidella elaeochroma (Ach.) M. Choisy, Evernia prunastri (L.) Ach., E. mesomorpha Nyl., Hypogymnia physodes (L.) Nyl., Pleurosticta acetabulum (Neck.) Elix & Lumbsch, Ramalina dilacerata (Hoffm.) Hoffm., R. pollinaria (Westr.) Ach., Parmelina quercina (Willd.) Hale, Physcia adscendens (Fr.) H. Olivier, Ph. tenella (Scop.) DC., Pseudevernia furfuracea (L.) Zopf, Ramalina fraxinea (L.) Ach., Rinodina colobina (Ach.) Th., Scоliciosporum chlorococcum (Graewe ex Stenh.) V?zda, Xanthoria parietina (L.) Beltr. and others). Morphological structure of oak bark and its neutral pH create favorable conditions for the development of lichens, but a small range of species of lichens, that we noted, is an evidence of the small age of these plants. Conclusions Representation of natural and artificial forest stands promotes epiphytic lichens spreading in the region. The species composition and environmental growth conditions affect the quantity and quality of lichens that colonize the bark.